ILUSTRASI PSIKOPAT PADA FILM THE ORPHAN KARYA JAUMME COLLET-SERRA 2009 - Taroreh, Naftharia Meilani Sarah; Wantasen, Isnawati L.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â This research is entitled â€œIlustrasi Psikopat dalam Film The Orphan oleh Jaume Collet-Serraâ€. It is written to fulfill the requirement of accomplishing bachelor degree in English Department Faculty of Humanities Sam Ratulangi University. The focus of this research is psychopath behavior and the impact of psychopathic on other characters in the film The Orphan. This research uses descriptive qualitative method by Nasir (1998:63), and the writer uses two theories, the theory of psychopath from Lyyken (1957) and the theory of character from Edgar V. Roberts (1983) to identify, describe and analyze the data. Based on the analysis of Ilustration of psikopath in the film The Orphan. It was found that Psychopaths have a brave nature in taking cruel actions and they can do so without having the slightest guilt. In this film there are 4 types of characters from a psychopath, namely failure to conform to social norms (Failure to conform to social norms), as directed by repeated lies (Deceitfulness), Aggressive traits exhibited by physical or repeated attacks (Aggresiveness), and are consistently irresponsible as demonstrated by repeated failure to maintain consistent work behavior (Consistent irresponsibility).Keywords: Psychopath, Literature and Psychology, Film, The Orphan